PENGARUH PERSEPSI SISWA ATAS LINGKUNGAN SEKOLAH DAN DISIPLIN BELAJAR TERHADAP PRESTASI BELAJAR BAHASA INGGRIS - Gola Kusnarti; Supeno Supeno (Universitas Indraprasta PGRI, 2019)
The purpose of this study is to determine the effect of Student Perceptions on School Environment and Discipline Learning Together Against English Learning Achievement, the effect of students' perceptions of school environment on English learning achievement, the effect of learning discipline on English learning achievement. The research method used is descriptive survey method, which is a research method that takes samples from a population and uses a questionnaire as a data collection tool. The samples are two classes from two different schools, namely Mulia Hati Insani Warunggunung Vocational School, and Mathala'ul Anwar Cibuah Vocational School. The results of this study indicate that: 1) there is a significant influence of students' perceptions of the school environment and the discipline of learning together on the achievement of English learning for students of SMK Lebak in Banten Province. This is evidenced by the acquisition of Sig. 0.043 <0.05 and Fcount = 8.3329. 2) There is no significant effect of students' perceptions of the school environment on the achievement of English learning students of Vocational Private Schools in Lebak Regency, Banten Province. This is evidenced by the acquisition of Sig. 0.679> 0.05 and t = 0.415. 3) There is a significant influence of learning discipline on the achievement of English learning of students of Vocational Schools in the Lebak Regency of Banten Province. This is evidenced by the acquisition of Sig. 0.038 <0.05 and t count = 2.869.Key Words: environment; discipline; student achievement; learning English; private vocational school